Uso de polímeros condutores na protecção catódica em estruturas de aço - A. Mendes (2009)
The objective of this study is the development of an anticorrosive primer with less zinc content. Partial substitution of zinc by electrical conductive resins should rend the process more cost effective. In the present work, a standard epoxy coating with a high zinc content (93 wt. % as specified in the Steel Structures Paint Council), was used as a starting formulation in which part of the zinc was replaced by a resin based polyaniline (Emeraldine salt Long chain, grafted to Lignin). This new formulation was produced with less 20 wt. % of zinc regarding the standardformulation, and the addition of 3 wt. % of polyaniline. The coating characterization, concerning the anticorrosive properties, was performed using two distinct techniques: (i) salt fog spray test and (ii) a new technique based on electrochemical impedance spectroscopy (EIS), the so-called AC-DC-AC method. This technique proved to be accurate and much faster (in less 24 hours) than salt fog spray tests; similar results were obtained for the two methods.Based on the results, it was observed that coatings with polyaniline perform slightly better in terms of corrosion protection of steel structures than the standard zinc based formulations.